PENGARUH MANAJEMEN KELAS TERHADAP HASIL BELAJAR PESERTA DIDIK - Syukriani Anwar; Hikma; Sulkifli (Wasīlah: Journal Of Sharia Sciences, 2026)
Classroom management is an effort by teachers to manage the teaching and learning process so that it can run effectively. In this context, teachers are required to have the skills to make decisions, understand classroom conditions, identify problems, and take appropriate actions to improve the learning environment. Several aspects that need to be considered in classroom management include the characteristics of the class, the dynamics that occur within it, the learning situation, and the teacher’s ability to act selectively and creatively. In addition, classroom management can also be defined as the teacher’s ability to organize, guide, and manage students’ learning activities so that they become better. With proper management, the learning process can run in an orderly and effective manner. Classroom management is carried out consciously and in a planned way, covering various aspects such as lesson preparation, student management, the use of facilities and infrastructure, the use of learning media, classroom arrangement, creating a conducive learning atmosphere, and time management. The main objective of classroom management is to achieve the predetermined learning targets, such as core competencies, basic competencies, and indicators. With good classroom management, the learning process can be more directed, and students’ learning outcomes can become more optimal and effective.